2009
DOI: 10.1002/ppp.663
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in vegetation composition, surface height and thaw depth in polygon mires in the Yakutian Arctic (NE Siberia): a microtopographical characterisation of the active layer

Abstract: Mapping of two low‐centred ice‐wedge polygons in the Yakutian tundra (NE Siberia) along a regular grid with 1‐m spacing revealed large spatial variability in thaw depths and strong correlation with relief, water and vegetation. Average thaw depths in polygon ridges (23 cm and 31 cm) were smaller than in depressions (33 cm and 40 cm, respectively). The greatest thaw depths, however, were also found in the ridges and probably result from thermal erosion by water flow. Copyright © 2009 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 22 publications
4
65
2
Order By: Relevance
“…During the last decade studies have been conducted with a special focus on the carbon content (Zubrzycki et al, 2013), and on the net ecosystem CO 2 exchange, for example in low-centred polygons on Samoylov Island (Runkle et al, 2013). Other investigations have used polygon sediments to trace short-term changes in vegetation (De Klerk et al, 2011) and long-term changes in landscape dynamics (Minke et al, 2009;Zoltai andVitt, 1990, 1995). While previous studies have identified the general processes that lead to the formation of polygon mires, the polygon dynamics and associated driving factors remain only poorly understood.…”
Section: R Zibulski Et Al: River Flooding As a Driver Of Polygon Dymentioning
confidence: 99%
“…During the last decade studies have been conducted with a special focus on the carbon content (Zubrzycki et al, 2013), and on the net ecosystem CO 2 exchange, for example in low-centred polygons on Samoylov Island (Runkle et al, 2013). Other investigations have used polygon sediments to trace short-term changes in vegetation (De Klerk et al, 2011) and long-term changes in landscape dynamics (Minke et al, 2009;Zoltai andVitt, 1990, 1995). While previous studies have identified the general processes that lead to the formation of polygon mires, the polygon dynamics and associated driving factors remain only poorly understood.…”
Section: R Zibulski Et Al: River Flooding As a Driver Of Polygon Dymentioning
confidence: 99%
“…Similarly, polygonal tundra and soils similar to those investigated in the eastern part of Samoylov Island can be expected to form on other Arctic river terraces that are no longer flooded on a regular basis. However, at polygonal tundra sites in which fluvial and aeolian sedimentation processes are less active than in the Lena River Delta, the soils often show greater autochthonous accumulations of organic matter (e.g., Minke et al, 2007Minke et al, , 2009). The Soil Organic Carbon Content (SOCC) was 28 kg m −2 for the upper 100 cm and 73 kg m −2 for the upper 300 cm of one core on Samoylov Island, which is comparable to the average SOCC figure for turbel soils (turbel soils contain on average 32.2 kg m −2 in first the 100 cm, with a range from 1 to 126 kg m −2 , Tarnocai et al, 2009).…”
Section: Land Cover Classification and Soilsmentioning
confidence: 99%
“…While Carex concolor is very tolerant with respect to water supply and has a high presence both in wet polygon depressions (97 %) and on dry polygon ridges (90 %), with coverage levels of 12 % and 4.4 %, respectively, the previously mentioned moss species (Tomentypnum nitens, Aulacomnium palustre, and Aulacomnium turgidum) prefer intermediate moisture conditions such as those found on hummocks in depressed polygon centres, or on the lower parts of ridge slopes. Minke et al (2009) The fourth vegetation community on Samoylov consists almost entirely of Arctophila fulva, growing in water in the shallow parts of the lakes.…”
Section: Vegetationmentioning
confidence: 99%
“…1d). The method of surveying ice-wedge polygons in high spatial resolution was adapted from de Klerk et al (2009) and Minke et al (2009). Transects of 1)1 m plots were laid through Herschel, Komakuk and Roland polygons (Fig.…”
Section: Fieldworkmentioning
confidence: 99%